Living with and responding to risk in the Uttarakhand Himalayas: A call for prioritizing lived experiences in research policy praxis. (September 2020) - Ritu,
Abstract: Based on primary data collected from three hamlets located in the Himalayas of Uttarakhand, India, this paper brings together pieces of the communities' grounded experiences of living with risks. It contributes towards a fuller and more nuanced picture of their encounters (both brief and prolonged) with adverse environmental events that are part and parcel of life in this region. The study with an aim of benefitting the very communities being studied draws on an inductive research methodology which prioritizes lived realities among heterogeneous communities. The case studies illustrate the ground reality of life in a multi-hazardous environment that exposes communities to a diversity of adverse situations. The cases discussed exemplify the undeniable reality of ongoing socio-ecological processes that affect hill people in different forms and intensities over time and space (disaster risk reduction focus), which further invites a broadening of the more conventional view that sees disasters as aberrations that occur in an otherwise stable landscape (an event focus). While for some this reality manifests as mega-events that have a clear beginning and end, for others they take the form of silent disasters, sluggish small scale and recurring, but whose cumulative impacts are no less disastrous. While the former grabs attention and relief work, the latter deemed as seasonal occurrences, often go under the official radar and fail to get the engagement they deserve. Gradually these events erode livelihood security and extract an immense psycho-social toll, de-stabilising people's sense of security, rootedness and future prospects. By bringing forth fresh field-based perspectives that speak to the mundane tribulations of mountain people, nuanced by caste, gender, and remoteness, this paper contributes to research-policy praxis by bringing alive the multi-layered and multi-dimensional lived experience of adverse environmental events.